CROWDFUNDING AS FINANCING METHOD: POTENTIAL AND ASPECTS OF REGULATION - Afonin,; Lobazova,; Kiseleva, Alla; Tarasov, Yuriy; Goncharov, Vitaly (Revista Inclusiones, 2020)
The present paper explores the aspects and practical issues of crowdfunding as one of the modern investment techniques supporting many social processes and business ideas. Amid the wide adoption of digital technologies in many areas of social life, crowdfunding progresses to a new level of consideration and the issues of regulation arise in the most advanced economies. The purpose of this study is to analyse the practical issues arising before the lawmakers and to develop recommendations on elaborating efficient organisational and legal solutions. The authors analyse potential applications of crowdfunding, international regulatory approaches and the projected legal norms of the Russian draft law on digital technologies in crowdfunding. The vast potential of innovative technologies in crowdfunding is outlined, as well as the risks involved. The outlook is analysed as to the development of legal regulation concerning digital technologies in crowdfunding and the problems arising in the area. It is observed that for now, there is yet no developed legal regulation of crowdfunding in the Russian Federation. However, one can already find successful examples of crowdfunding applications in global social and business practices. Conclusions are drawn and the outlook is described as to the development of crowdfunding regulation associated with the application of blockchain technology. The authors offer an assessment of legal regulatory options and propose to adopt the most plausible solutions for the Russian legal framework.